Dredging in an estuary causes contamination by fluid mud on a tourist ocean beach. Evidence via REE ratios. (October 2020) - Mirlean, N.; Calliari, L.; Johannesson, K.
Abstract: Deposits of fluid mud on wave-dominated beaches are rare. Where they happen frequently and periodically, they can be associated with anthropic processes that bring fluid mud to the shoreface and surf zone. To determine the reason for the frequent deposition of fluid mud at Cassino Beach (Southern Brazil) in the 2014–2020 period, the La/Eu and Gd/Yb ratios in marine, beach, and adjacent Patos estuary sediments were investigated. Mud from the beach showed similar ratios of REE to dredged sediments from the harbor basin and navigation channel within the estuary. Industrial and port activity changes REE ratio in sediments of the navigation channel, and they are distinct from naturally deposited marine and estuarine sediments. We conclude that the mud deposition events at the beach are most likely associated with dredging processes in the estuary especially where overflow is the source of fluid mud on the beach shoreface. Highlights: A frequent fluid mud deposition on beaches could reflect anthropogenic activities. The La/Eu and Gd/Yb ratios can be used as fingerprinting markers in sediments. The overflow dredging procedure should be avoided to prevent fluid mud contaminations.